2005
DOI: 10.1007/s10592-005-9028-2
|View full text |Cite
|
Sign up to set email alerts
|

Geographic variability in mitochondrial introgression among hybridizing populations of Golden-winged (Vermivora chrysoptera) and Blue-winged (V.opinus) Warblers

Abstract: The rapidly declining Golden-winged Warbler (Vermivora chrysoptera) is of conservation concern owing in part to hybridization with the closely related Blue-winged Warbler (V. pinus). These species hybridize extensively in eastern North America and over the past century the Blue-winged Warbler has displaced the Golden-winged Warbler from substantial regions of its historic breeding range. A previous study suggested that these genetic interactions result in rapid and asymmetric introgression of Blue-winged Warbl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
43
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 42 publications
6
43
1
Order By: Relevance
“…Smaller samples from Michigan and Ohio also failed to show evidence of asymmetric introgression. Likewise, similar analyses by Dabrowski et al . (2005) determined bidirectional gene flow and long‐term persistence of chrysoptera mtDNA haplotypes in a sympatric population in New York with an extensive history of contact between the species.…”
Section: Introductionsupporting
confidence: 81%
“…Smaller samples from Michigan and Ohio also failed to show evidence of asymmetric introgression. Likewise, similar analyses by Dabrowski et al . (2005) determined bidirectional gene flow and long‐term persistence of chrysoptera mtDNA haplotypes in a sympatric population in New York with an extensive history of contact between the species.…”
Section: Introductionsupporting
confidence: 81%
“…Introgression between newts Triturus cristatus and Triturus marmoratus is found in the area of recent species replacement, but is absent in other areas (Arntzen and Wallis, 1991). At a hybrid zone between two warbler species, predominantly Vermivora chrysoptera mtDNA haplotypes are found in hybrids at the leading edge of a Vermivora pinus expansion (Dabrowski et al, 2005) and cytonuclear disequilibrium is also found at a crayfish Orconectes rustica-Orconectes propinquus hybrid zone. Two studies of deer, Cervus elaphus and alien Cervus nippon nippon, show introgression in both taxa (Abernethy, 1994;Goodman et al, 1999), but the expanding alien taxon shows higher levels of introgression which are uniform across its range, while introgression is lower in C. elaphus and more common near the region of overlap (Goodman et al, 1999).…”
Section: Relictual Populationsmentioning
confidence: 99%
“…128 the expanding Blue-winged Warbler. However, follow-up studies in this system have been more optimistic: mtDNA introgression seems to be more or less symmetrical within most contact regions (Shapiro et al 2004, Dabrowski et al 2005, whereas foreign nDNA may predominantly move into the blue-winged invaders (Vallender et al 2007), not into the golden-winged invadees. Although Vallender et al's (2007) hybrid zone samples were biased toward phenotypically pure Golden-winged Warblers (which were, on average, composed of 30% introgressed nDNA), the one phenotypic Blue-winged Warbler they examined was made up of 85% introgressed nDNA, which suggests much higher introgression rates into the invaders.…”
mentioning
confidence: 99%